Studies of weeding frequency in cassava in cameroon - Ambe, J.T.; Agboola, A.A.; Hahn, S.K. (Informa UK Limited, 1992)
The critical period of weed interference was investigated from 1982–1985 In two local cassava cultivars in Cameroon. Unweeded plots had more than 90% losses and were infested by birds and rodents which caused much damage to the fresh storage roots. One weeding round was not an effective treatment. Two weeding rounds at 4 and 12 weeks after planting (WAP) gave yields twice that with two weedings at 12 and 20 WAP. Three weedings at 4, 12 and 20 WAP gave the best yields: 11 t/ha and 17 t/ha for the red and white‐skinned cultivars, respectively. The highest storage root number was also recorded for the same treatment